Dietary Yucca schidigera Extract Supplementation During Late Gestating and Lactating Sows Improves Animal Performance, Nutrient Digestibility, and Manure Ammonia Emission - Chen, Fang; Lv, Yantao; Zhu, Pengwei; Cui, Chang; Wu, Caichi; Chen, Jun; Zhang, Shihai; Guan, Wutai (Frontiers in Veterinary Science, 2021)
This study was conducted to investigate the effect of dietary Yucca schidigera extract (YSE) supplementation to animal performance, nutrients digestibility and ammonia emission of manure. Total 80 sows were randomly divided into 4 groups and fed with either control, control + 0.06% YSE, control + 0.12% YSE or control + 0.24% YSE diet from day 80 of gestation to day 21 of lactation. The results showed that dietary YSE supplementation resulted in trends toward a reduced number of stillbirth piglets (P = 0.08), weak piglets (P = 0.06), pre-weanling mortality and diarrhea, and improved apparent digestibility of dry matter. Besides, YSE supplementation significantly increased catalase activity while decreasing malonaldehyde levels in sow and piglet blood. Furthermore, the loss of total nitrogen, urea nitrogen and ammonia nitrogen in sow manure were significantly reduced with supplementation of YSE. In summary, supplementation of YSE in sow diet during gestation and lactation could improve sow and litter performance, nutrient digestibility, and reduce nitrogen loss in sow manure during storage.